A CRITICAL DISCOURSE ANALYSIS OF GIBRAN’S RESPONSE TO PANDJI’S POLITICAL SATIRE - Hassika Laila; Yeni Artanti; Susana Widyastuti; Sulis Triyono (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study explores stand-up comedy as a medium for expressing socio-political issues and examines how political figures respond to such satire in digital media. This study scopes the discourse and power relations in Gibran Rakabuming’s response to Pandji Pragiwaksono’s satire in his Mens Rea show, which was recorded and published on Netflix and Tretan Universe YouTube channel. Previous studies of political satire have focused mainly on the construction of humour. This study fills the gap by examining the strategic responses of targeted politicians. Using a descriptive qualitative approach, this study analyzes micro-level linguistic features through Halliday’s Systemic Functional Linguistics (SFL) metafunctions, ideational, interpersonal, and textual and examines how language constructs meaning and sociocultural practices through Critical Discourse Analysis (CDA), drawing on Fairclough’s framework of representation, relations, and identity. Gibran’s composed demeanor functions discursively as a strategy of political deflection. His serenity, laughter, and simple language transform political criticism into harmless biological humor framed as natural and innocent. This strategy exemplifies ‘soft hegemony,’ whereby politicians employ humor and self-deprecation to diffuse critique and maintain authority. This study greatly advances the field of political discourse by broadening the scope of application of SFL and CDA frameworks to informal digital multimodal interactions, which are usually dismissed as trivial entertainment but are in fact highly complex and sophisticated sites for ideological negotiation and power reproduction.